ChemInform Abstract: Three New 24‐Nortriterpenoids from the Roots of Ilex asprella. Issue 20 (20th May 2014) - Jiang, Kun; Bai, Jun‐Qi; Chang, Jun; Tan, Jun‐Jie; Qu, Shi‐Jin; Luo, Hong‐Feng; Tan, Chang‐Heng; Zhu, Da‐Yuan
Abstract isolation and structure of new terpenoids, asprellols A—C (Ib, II, Ia, resp.)